2002
DOI: 10.1177/089686080202200409
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gastric Emptying Rate and Nutritional Status in Patients Treated with Continuous Ambulatory Peritoneal Dialysis

Abstract: ♦ Objective To estimate gastric emptying rate in continuous ambulatory peritoneal dialysis (CAPD) patients, with or without indwelling dialysate, and to evaluate if there is an association between gastric motility and nutritional status. ♦ Design Single-center cross-sectional study. ♦ Setting Peritoneal Dialysis Unit, Medical Faculty, Jagiellonian University Hospital, Krakow, Poland. ♦ Patients and Methods 20 end-stage renal disease patients [11 F, 9 M; mean age 50.1 ± 11 years; treated with CAPD for median 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Specific factors that might be associated with poor appetite include absorption of glucose from PD solutions and abdominal fullness induced by the dialysate (Chung, Carrero, & Lindholm, 2011). Stompor et al (2002) also reported delay of gastric emptying as another explanation for anorexia in PD patients. We also found an association between underlying cardiovascular disease and diminished appetite among PD patients in the current study, which did not emerge in previous studies conducted in hemodialysis patients (Carrero et al, 2007;Kalantar-Zadeh et al, 2004).…”
Section: Appetite Statusmentioning
confidence: 98%
“…Specific factors that might be associated with poor appetite include absorption of glucose from PD solutions and abdominal fullness induced by the dialysate (Chung, Carrero, & Lindholm, 2011). Stompor et al (2002) also reported delay of gastric emptying as another explanation for anorexia in PD patients. We also found an association between underlying cardiovascular disease and diminished appetite among PD patients in the current study, which did not emerge in previous studies conducted in hemodialysis patients (Carrero et al, 2007;Kalantar-Zadeh et al, 2004).…”
Section: Appetite Statusmentioning
confidence: 98%
“…Gastroparesis is associated with gastrointestinal symptoms such as dyspepsia, early satiety, bloating, vomiting, and gastroesophageal reflux. These symptoms contribute to decreased nutritional intake in no small measure and are an important cause of malnutrition in patients with chronic kidney disease ( 71 ). Dialysis therapy and the use of prokinetic agents such as erythromycin or metoclopramide have been shown to improve gastrointestinal motor function in these patients ( 70 , 74 ).…”
Section: Pathophysiologic Mechanisms Of Protein Energy Wasting In Chrmentioning
confidence: 99%
“…[ 18 ] A Swedish study,[ 6 ] employing fluoroscopic evaluation of GE of spherical radiopaque markers, has reported a 36% prevalence of delayed GE among CKD patients. Barring a Brazilian study,[ 21 ] several previous studies[ 5 6 9 11 12 22 ] have reported an increased prevalence of delayed GE among CKD patients. Delayed GE was more frequent in male CKD patients in the Swedish study,[ 6 ] similar to findings in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have evaluated GE in patients with CKD, most of them have involved end-stage kidney disease patients on either maintenance hemodialysis[ 3 6 7 8 10 ] or peritoneal dialysis. [ 6 7 8 11 ] To the best of our knowledge, only one small Indian study has evaluated GE in non-diabetic CKD patients so far. [ 5 ] However, the prevalence of upper gastrointestinal symptoms and abnormalities of GE have not been studied systematically in different stages of non-diabetic CKD, among Indian patients.…”
Section: Introductionmentioning
confidence: 99%